Estimasi Emisi Gas Rumah Kaca(GRK) Terhadap Konsumsi Energi di Provinsi Bali - Adiputra, Ida Bagus Bawa; Hartati, Rukmi Sari; Ariastina, Wayan Gede (Majalah Ilmiah Teknologi Elektro; Vol 17 No 3 (2018): (September - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2018.v17i03.P09, 2018)
Electrical energy is one concerning lives of the people, then provision must be able to ensure the availability of a sufficient number, reasonable prices and good quality. Until now, the use of fossil fuels is still quite high as a primary energy source that is utilized in the process of generating electricity. It has an impact on climate change so that Greenhouse Gases (GHG) arise. The composition of energy use at the end of the projection (2030) uses LEAP software Household consists of the sector amounted to 5.865,1 GWh, Industrial sector of 490.380,6 GWh, Public (Commercial) sector of 3.547,5 GWh, and from Transportation sector as big as 7.220.937,8 BoE. The projection of GHG emissions using LEAP software shows that emissions in 2030 for the Household sector amounted to 8.9115 million tCO 2 eq, the Industrial sector amounted to 1212.3964 million tCO 2 eq, the Transportation sector amounted to 26.2161 million tCO 2 eq, and when the generation of electricity was 33,0955 million tCO 2 eq. So the total GHG emissions generated are 1,280,6196 million tCO 2 eq, this amount is an accumulated increase from 2015 of 61.4533 million tCO 2 eq. To suppress the amount of increase of that size, efforts need to be made such as promoting the use of environmentally friendly energy. Reduce the use of private vehicles and switch to public transportation. The government must also support by providing environmentally friendly mass transportation facilities.